A user-centric approach to dynamic adaptation of reusable communication services. Issue 2 (April 2016) - Allen, Andrew; Costa, Fábio; Clarke, Peter
Abstract The pervasiveness of electronic devices coupled with increasing resources within these devices has aided the explosion of available software services. While reusable software services have become more accessible and the cost of using these services has become cheaper, the increased number of services and access methods also increases the complexity for the user of these services, demanding too much attention from the user. On the other hand, automation can alleviate some of the complexity issues but at the expense of user control. We propose a balance between smart reusable integration, automation and user controllability, through a dynamically adaptive user-centric approach that utilizes goal-oriented intent modeling. This work leverages the convergence of services and providers for the user through reuse, autonomic adaptation of services to relieve the user's of laborious and tedious tasks, while ensuring that the user's end-goal remains central at all times. We applied our approach to the domains of collaborative communication as demonstration of the feasibility of the approach.